Community Engagement Program Odapus (People with Lupus) ‘My Lupus’ Support Group Based in Wedomartani - Ayu Paramaiswari Nurtjahjo; Sri Awalia Febriana; Noor Asyiqah Sofia (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2021)
Lupus is one of the autoimmune rheumatic diseases that require long-term treatment, can potentially be life-threatening, but is still unknown to the general public. However, there are various problems encountered by odapus (orang dengan lupus = people with lupus) and their companions during treatments. This program is established to create a support group for odapus, their companions, and associated medical professionals by organizing counseling and focus group discussion (FGD) during March until November 2018 in Wedomartani, as well as providing information regarding Lupus and its problems on www.jogjalupuscare.com and Lupus bulletin. Simultaneously, several studies were conducted to evaluate psychological factors of lupus survivors. Pre-test and post-test scores were used as evaluations of counseling and FGD, the results were analyzed using paired t-test or Wilcoxon test, whereas the research used Pearson or Spearman correlation test. The pre-test score increased from 86.81 to 100. There was a significant relationship between disease activity and depression scores, quality of life and insomnia scores, as well as anxiety and depression levels with the quality of life (p <0.05). There was no correlation between disease activity and anxiety scores. Education and counseling are some of the main pillars in lupus treatment, while psychological factors faced by odapus during treatments cannot be ignored.